Susac Syndrome and Pregnancy - Yazan Al-Hasan; Justin L. Hoskin; John C. Wolf; Kamala Saha (Case Reports in Neurological Medicine)
Susac syndrome (SuS) is a rare poorly characterised disorder that affects the brain, retina, and cochlea. Here, we present a case of a 31-year-old pregnant female with a new diagnosis of SuS that was successfully managed to 36 weeks of gestation with minimal disease burden to both the mother and newborn. She was treated initially using intravenous methylprednisolone followed by oral prednisone, and intravenous immunoglobulin (IVIg). We stress the importance of a multidisciplinary approach, involving both neurology and maternal-fetal medicine, and provide guidance in navigating the various options for immunosuppressive therapy during pregnancy.